In-silico identification of anti-cholera phytochemicals from Indian medicinal plants - Khalilur Rahman; Yasmin Akter; Md Selim Reza; Md. Al Amin Pappu; Md. Rezaul Karim; Marzia Sultana; Mohammad Tarequl Islam; Munirul Alam; Md Nurul Haque Mollah; Md. Mamun Monir (PLoS ONE, 2026)
Cholera is a severe diarrheal disease caused by ingestion of food or water contaminated with pathogenic Vibrio cholerae . Treatment for cholera includes rehydration therapy and antibiotics to avert death and reduce bacterial burden to prevent rapid transmission of the disease. In addition, in Indian subcontinent, there is historical evidence of using plants for treating cholera. This study was designed to investigate the cholera toxin-inhibitory properties of phytochemicals sourced from Indian medicinal plants. For this, three reported genotypes of cholera toxin subunit B (ctxB) associated with 7PET V. cholerae O1 El Tor strains were used as targets in molecular docking. Analysis results showed strong binding affinities (≤−7.5 kcal/mol) for 298 out of 7,607 phytochemicals, with minor variations for the ctxB genotype-specific targets. Multiple phytochemicals from the same plants were identified with high binding affinities, e.g. , 101 from Morus alba, 24 from Citrus aurantium, 17 from Emblica officinalis, and 16 from Capsicum annuum . However, further analyses, including drug-likeness, pharmacokinetics, and toxicity, identified five promising phytochemical candidates, namely, Abyssinone V ( Azadirachta indica ), Diosgenin ( Achyranthes bidentata ), Yamogenin ( Borassus flabellifer ), and two other unnamed phytochemicals (one from Azadirachta indica and one from Morus alba ) for cholera toxin inhibition. Molecular dynamics simulation using YASARA and GROMACS showed structural stability of the ctxB-phytochemical complexes, while exhibiting adaptive rearrangements of ligand within the active binding sites of the proteins. In the simulations, MM-PBSA binding free energies showed a favorable total binding energy for the complexes. Per-residue energy decomposition analysis identified different highly contributing sets of amino acids to the binding energy with variation for both ctxB genotypes and phytochemicals, suggesting bacterial evolutionary changes may affect binding patterns of the drug candidates. This study suggests five inhibitors of cholera toxin with varying genotypes, which may have potential as an alternative medication for cholera.